2014
DOI: 10.1038/nature14112
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-negative progenitors mobilize to regenerate lung epithelium after major injury

Abstract: Broadly, tissue regeneration is achieved in two ways: by proliferation of common differentiated cells and/or by deployment of specialized stem/progenitor cells. Which of these pathways applies is both organ and injury-specific1–4. Current paradigms in the lung posit that epithelial repair can be attributed to cells expressing mature lineage markers5–8. In contrast we here define the regenerative role of previously uncharacterized, rare lineage-negative epithelial stem/progenitor (LNEPs) cells present within no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
730
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 617 publications
(797 citation statements)
references
References 24 publications
41
730
5
1
Order By: Relevance
“…Indeed, different regions of the mouse airway may model different aspects of human cell biology and disease to varying degrees, despite the histological similarity of murine tracheal and human airway epithelium. Recent studies in mice have also demonstrated the presence of small numbers of basal-like progenitor cells in the distal airways, even at steady state (Kumar et al, 2011;Vaughan et al, 2015). Remarkably, the number of such cells is increased in the small airways and alveoli following severe injury caused by H1N1 influenza injury or bleomycin (Vaughan et al, 2015;Zuo et al, 2015).…”
Section: Basal Cellsmentioning
confidence: 96%
See 2 more Smart Citations
“…Indeed, different regions of the mouse airway may model different aspects of human cell biology and disease to varying degrees, despite the histological similarity of murine tracheal and human airway epithelium. Recent studies in mice have also demonstrated the presence of small numbers of basal-like progenitor cells in the distal airways, even at steady state (Kumar et al, 2011;Vaughan et al, 2015). Remarkably, the number of such cells is increased in the small airways and alveoli following severe injury caused by H1N1 influenza injury or bleomycin (Vaughan et al, 2015;Zuo et al, 2015).…”
Section: Basal Cellsmentioning
confidence: 96%
“…Recent studies in mice have also demonstrated the presence of small numbers of basal-like progenitor cells in the distal airways, even at steady state (Kumar et al, 2011;Vaughan et al, 2015). Remarkably, the number of such cells is increased in the small airways and alveoli following severe injury caused by H1N1 influenza injury or bleomycin (Vaughan et al, 2015;Zuo et al, 2015). Finally, it is likely that each of the cell types of the airway epithelium have additional functions beyond that Anatomical and cellular differences between murine and human lung.…”
Section: Basal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inability of these cells to differentiate leads to the honeycomb-like structures. 29 Recently, it was shown that these Krt5 pods are not observed during lung injury induced by less virulent X31 influenza in mice, suggesting that the severity of lung injury may dictate the cellular repair process. 31 It is possible that the persistent ER stress observed herein may modulate the ability of the progenitor cells to differentiate and to form alveolar structure.…”
Section: Discussionmentioning
confidence: 99%
“…Basal cells expressing detectable levels of Trp63 and Krt5 are only present in trachea and main stem bronchi. Lineage-negative epithelial progenitors (LNEPs) have been proposed for the distal airways (Vaughan et al, 2015), which in the mouse are known as bronchioles as they lack associated cartilage. There is evidence that the Club cell population is heterogeneous, with a few cells in the bronchioalveolar duct junction (BADJ) and alveoli (marked with an asterisk) co-expressing Scbg1a1 and Sftpc (Kim et al, 2005;Rawlins et al, 2009).…”
Section: Basal Progenitor Cellsmentioning
confidence: 99%